A Note on Realism, by Robert Louis Stevenson - Fernandes dos Santos, Thaís (2020)
We propose a full translation from English into Brazilian Portuguese of the literary essay entitled A Note on Realism, written by the Scottish poet and writer Robert Louis Stevenson (1850-1894). The essay was originally published in 1912 as part of Essays in The Art of Writing (1917). In it, Stevenson addressed issues of writing technique associated with elements of style and form as applied to works of literature in order to reveal the originality of the writer’s literary project.